SARCASTIC EXPRESSIONS IN MERIAQ-MERIQU DIALECT OF SASAK LANGUAGE: PRAGMATIC STUDY - Sutarman - (LPPM Universitas Bumigora Mataram, 2018)
This research aims at studying the pragmatic use of sarcasm in Meriaq-Meriqu dialect of Sasak language. This research is a qualitative research. The data are collected via two techniques – participant observation and unstructured interview. The data are then analyzed via interactive model which consists of three main points: data reduction, data presentation and data clarification. The results show that there are three kinds of sarcastic expressions in Meriaq-Meriqu – word form, phrasal form and clause form. In word form, the reference used as sarcastic word is mostly from animal, characters and parts of body while the reference in phrasal forms is mostly taken from part of body, animal and characters. The clause form of sarcasm is divided into two kinds- direct and indirect sarcasm. In terms of functions, sarcasms have five functions- expression of intimacy, informal address, expression of anger, insinuation and humiliation.